Methods of test for orthoboric acid (boric acid), diboron trioxide (boric oxide), disodium tetraborates, sodium perborates and crude sodium borates for industrial use. Determination of chromium content of boric acid, boric oxide and disodium tetraborates Part 14, (28th February 1979) - British Standards Institution,
No abstract available